(untitled) (CIPEEX, 2025)
INTRODUCTION: Infant mortality, when recurrent in a specific epidemiological stratum, often reflects various incongruences in the exercise of the broad notion of health. Although the reduction of this scenario is proposed by the UN’s 2030 Agenda, in Brazil, investigating the effectiveness of public health strategies is of utmost importance. OBJECTIVE: To analyze preventable child deaths in the state of Goiás, comparing the pre-pandemic period with the pandemic period, and to evaluate the impacts of this crisis on the 2030 Agenda goals. METHODOLOGY: This research is understood as a retrospective study of an exploratory and descriptive nature with a quantitative approach. The records used to fulfill the objective of interest were obtained from the Department of Informatics of the Unified Health System (DATASUS) regarding statistics of infant mortality from preventable causes in children aged 0 to 4 years. RESULTS: The data collected show that infant mortality is currently more concentrated in the early neonatal period, with a large part of the deaths occurring in the first 24 hours of life. However, from 2020, the year the COVID-19 pandemic began to affect globally, some indicators showed significant variations. CONCLUSION: Given this scenario, the development of new studies with this population is suggested, adopting a qualitative approach, to guide the formulation of policies aimed at improving healthcare assistance.